Elaboración de mapas de zonificación según los niveles de presión sonora por tráfico urbano en Bogotá, Colombia : caso específico: UPZ 22 en la localidad de Barrios Unidos enfocado en una propuesta de infraestructura nueva (2016)
Noise pollution is the third most dangerous type of pollution at the global level, only overcome by contamination in water sources and air pollution (Trombetta, Coelho, & Szeremetta, 2006). Within the cities, much of the sound pressure emitted comes from ground transportation, air traffic and industrial activities. In Bogotá, mobile sources generate about 60% of the auditory pollution, while fixed sources generate the remaining 40% (Bogotá Mayoralty, 2014). The present study determines the exposure of the resident and floating population to high sound pressure levels coming from urban traffic in the Urban Planning Unit (UPZ) 22 of Barrios Unidos. This evaluation is performed by direct noise measurements along the UPZ road mesh, for two-hour time intervals at peak hours and two hours at vehicular traffic valley hours. Measurements were made with type I sound level meters, frequency a weighting and fast temporal weighting (F) following the guidelines of resolution 0627 of 2006. The point data obtained were subjected to a "Kriging / CoKriging" interpolation. The maps show that only 10.62% of the study area complies with the regulations, parks and recreation centers cover much of this percentage. In the comparison between peak hours and vehicle traffic hours, noise values were observed between 74 and 76.5 decibels (dBA) and between 73 and 75 dBA, respectively. Finally, the study proposes the relocation of residential, commercial, industrial and recreational infrastructure in the UPZ and the location of new infrastructure for environmental noise management such as vegetation screens, absorbent treatments, and time restrictions, among others.--Tomado del Formato de Documento de Grado.